(untitled) (The Pakistan Development Review, 2013)
Honourable Federal Minister for Planning, Development and Reform, his excellency Mr Ahsan Iqbal, the President, Pakistan Society of Development Economists, discussants, Dr Ashfaque Hasan Khan and Dr Rehana Siddiqui, Dr Durr-e-Nayab, distinguished ladies and gentlemen, let me say at the outset that it is a great privilege for me to be here and to be given this opportunity to deliver the Quaid-i-Azam Lecture. I regard this as a signal honour and I feel particularly privileged coming from India being able to speak in honour of the Quaid-i-Azam, the founder of this country. I want to express my gratitude for this particular privilege which I have been given. I also want to acknowledge the very warm sentiments expressed by his Excellency the Minister. I certainly believe that in this day and age we have to look forward, we have to look at the future and I think we have to erase some of the problems, demolish some of the barriers and the hindrances that have prevented South Asian cooperation in the past. So Sir, your words in that context are certainly appreciated and I would say that we have to put them into effect by ushering in a new future for this region. I want to mention that when I had the privilege of accepting the Nobel peace prize on behalf of Inter-governmental Panel on Climate Change (IPCC) in 2007 along with Mr Al Gore, in my acceptance speech I used a Sanskrit phrase which is Vasudhaiva Kutumbakam and that means the universe is one family. Now if the universe is one family, may I submit that, we particularly in Pakistan and India are really the core of that family. I believe the future lies in our ability to develop a model of economic growth and development that serves as an example for the rest of the world. Let me at the very outset say that we have been somewhat negligent and perhaps short sighted in emulating what has been established as a form of development in other parts of the world and I will say a little more about this as I move on. Let me start by referring to the definition of sustainable development which essentially comes out of the work of the Brundtland Commission that was completed in 1987 and it’s a very simple definition. It defines sustainable development as that form of development which allows the current generation to meet their own needs without compromising on the ability of future generations to meet their own needs. So, therefore, it essentially takes into account the issue of intergenerational equity. Whatever we do today should not be selfishly oriented by which we might meet more than our needs today